Clinical Spectrum and co morbidities of COVID 19 cases admitted at Anwer Khan Modern Medical College Hospital (AKMMCH): A Retrospective record review - Rahman, Md Atiqur; Haque, Sayed Tanjilul; Sharmin, Sadia; Kawser, Abu; Halder, Soma; Tajkia, Gule; Alam, Rajibul; Hoque, Ehteshamul; Rahman, Md Ekhlasur (Anwer Khan Modern Medical College Journal, 2021)
Background: Coronavirus diseases 2019 (COVID-19) caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has induced a sense of panic around the world and has been declared Pandemic by the World Health Organization (WHO) on the 11th March 2020. Bangladesh a country of 17 million people is not an exception regarding COVID-19. It has reported around five lacs COVID-19 cases with seven hundreds of deaths. In dealing those challenges AKMMCH has started opening a COVID-19 unit since July 2020 in order to render services for the admitted cases. Objective: The objective of this study was to explore the clinical spectrum of COVID-19 admitted cases, co morbidities, in addition to selected socio-demographic characteristics under review. Material and Methods: This descriptive type of retrospective record review was carried out among 1690 COVID-19 confirmed cases during the period of July-December 2020. Data were generated from hospital COVID unit admission records using a checklist. Data entry and statistical analysis were performed manually and by using computer. Results: The study revealed that majority of the cases was found within age 31-70 years with mean age 52.58 and standard deviation ± 21.7. About 76% cases were male and 24% were female. It also revealed that the clinical spectrum of COVID-19, 63% & 23% cases were moderate and severe cases respectively and only 9% were critically severe. Majority of the cases had chronic illnesses and the most common co-morbidities were Hypertension (44%), Diabetes (26%) and Cardiac diseases (10%). Conclusion: It may be stated that male persons with more than 52 years of age were mostly affected by COVID-19 diseases. Usually moderate to critically severe patient were admitted in hospital COVID-19 unit for better treatment. Hypertension, Diabetes, Asthma and Cardiac diseases were found as the most common co-morbidities. A comprehensive case management protocol involving allied disciplines (medicine, cardiology, and endocrinology) can be implemented towards improved services and better out come in particular. AKMMC J 2022; 13(1) : 3-7